Análisis de la incidencia del contenido del programa infantil educa en el desarrollo de los niños de 8 a 11 años en la ciudadela Alborada VI etapa - Quiroz Baquerizo, Francisca Elizabeth (2017)
The educational television in our country has not had the success expected by the public and its producers, due to diverse entertainment options such as show programs, news programs, reality shows, and educational proposals have been kept in the background. Nowadays, the era of technology with mobile devices with internet dominate the children, they have forgotten to see proposals of pedagogical content because they consider them boring or little innovative for the society in which they develop……..